Imaging Recommendations for Diagnosis, Staging, and Management of Prostate Cancer - Sable, Nilesh P.; Bakshi, Ganesh K.; Raghavan, N.; Bakshi, Hemang; Sharma, Rakesh; Menon, Santosh; Kumar, Prabhash; Katdare, Aparna; Popat, Palak (Indian Journal of Medical and Paediatric Oncology, 2023)
The Prostate Carcinoma Guidelines Panel have formulated these guidelines to assist medical professionals in the evidence-based management of prostate cancer. These have been formulated by a panel consisting of Indian multidisciplinary group of radiologists, uro-oncologists, urologists, radiation oncologists, medical oncologists, and pathologists. These recommendations present the best evidence available to the clinicians; however, using these recommendations will not always result in the best outcome. They aid in decision making for individual patients; however, these will never replace clinical expertise when making treatment decisions. Taking personal values and preferences or individual circumstances of patients into account is necessary for final treatment decision. Guidelines are not mandatory and should not to be referred as a legal standard of care.
Keywords: mpMRI prostate; prostate cancer; prostate cancer imaging guidelines; prostate cancer imaging recommendations; PSMAPETCT; PSMAPETMRI